Injecting Educational Element In Laws And Regulations Of Child Care Centres In Malaysia - Mashitah Abdul Mutalib; Nur Amalina Abdul Ghani (Global Academic Excellence, 2024)
The aim of regulating child care centres should not just be limited to providing protection in terms of the children’s safety and health. It should go beyond providing a ‘safe haven’ in order to enhance the potentials of the children. Therefore, the element of learning and education should be included as one of the legal requirements in regulating child care centres. This paper, therefore, examines the question of whether the educational element should be enacted in the legislative framework of Malaysian child care. The qualitative method is used in this study using document analysis. The laws and regulations on child care centres especially Child Care Centre Act 1984 are evaluated. Apart from the laws and regulations in Malaysia, analysis on international experiences of various jurisdictions which may be taken as lessons for Malaysia is also conducted in enhancing the laws and regulations of Malaysian child care. It is submitted that educational element is an important element to be embedded in laws and regulations governing child care centres in Malaysia early childhood apart from other legal requirements.